Metabolic profiling of Perilla leaves of different colors: insights into metabolite variation and bioactive compound distribution - Senouwa Segla Koffi Dossou; Qianchun Deng; Feng Li; Lei Wang; Nanjun Jiang; Habtamu Kefale; Rong Zhou; Donghua Li; Meilian Tan; Linhai Wang (BMC Plant Biology)
Abstract Background Perilla frutescens (L.) Britt. (Lamiaceae) leaves are essential culinary and medicinal herbs, native to East Asian countries. Three types of Perilla leaves, including green, green/purple and purple, are mainly found, and the leaf color is a critical attribute for consumer preferences. However, the extent of diversity and variability of metabolites in Perilla leaves of different colors remain elusive. Thus, in this study, we applied LC-QqQ-MS (liquid chromatography triple quadrupole tandem mass spectrometry)-based widely targeted metabolic profiling to investigate variation in the metabolite profiles of green (PF1), green/purple (PF2) and purple (PF3) Perilla leaves. Results We qualitatively and quantitatively identified a total of 1239 metabolites in Perilla leaves of different colors. Amino acids and derivatives (15.50%), flavonoids (14.77%), phenolic acids (12.19%), lipids (9.60%), carbohydrates and derivatives (8.47%), organic acids and derivatives (7.99%), nucleotides and derivatives (7.99%), and terpenoids (5.25%) were the major classes of metabolites in perilla leaves. In contrast to green leaves, the principal component analysis and correlation analysis revealed a considerable influence of genotypes for the variation in purple leaves’ metabolite profiles. Differentially accumulated metabolites (DAMs) analysis revealed that flavonoids, phenolic acids, and amino acids and derivatives were the major DAMs, and the phenylpropanoid pathway was the most differentially regulated. All DAMs, including four potential metabolic discriminative biomarkers, were screened out. In addition, we revealed the accumulation patterns of bioactive compounds in the leaves of different colors. It was noteworthy that most of the differentially accumulated flavonoids showed a higher relative content in PF3, followed by PF2 and PF1. Glycosylated cyanidins and delphinidins were identified as the key compounds responsible for the purple coloration of leaves. Finally, we found that the variation in glutamate metabolism may be one of the main contributors for variation in metabolite profiles and biological attributes of Perilla leaves of different colors. Conclusion Our results showed that the metabolic processes, mainly phenylpropanoid biosynthesis and amino acid metabolism, are differently regulated in green, green/purple and purple Perilla leaves. Furthermore, they offer valuable data for a comprehensive use of Perilla leaves and exploring gene-metabolites interactions in Perilla leaves.